Silicate application decreased methane emission from paddy soil under elevated UV‐B radiation. Issue 5 (6th October 2016) - Yunsheng, Lou; Yan, Meng; Lixuan, Ren; Lei, Wu; Yiwei, Zhang; Shidi, Zhao; Huaiwei, Zhu
Abstract: A pot experiment was conducted to investigate the effects of silicate application quantity and silicate fertilizer type on rice growth and methane (CH4 ) emission under elevated UV‐B radiation. The experiment was designed with two UV‐B radiation levels, i.e., reference UV‐B radiation (Ambient, A, 12.0 kJ·m −2 ·d −1 ), and elevated UV‐B radiation (Elevated by 20%, E, 14.4 kJ·m −2 ·d −1 ); with four silicate fertilizer levels, i.e., Si0 (no silicate application, 0 kg SiO2 ·ha −1 ), Si1 (sodium silicate, 100 kg SiO2 ·ha −1 ), Si2 (sodium silicate, 200 kg SiO2 ·ha −1 ) and Si3 (slag silicate fertilizer, 200 kg SiO2 ·ha −1 ). The results show that, silicate application could mitigate the depressive effect of elevated UV‐B radiation on rice growth and increase the tiller number, and dry weight of shoot and root biomass. Silicate application promoted rice growth, which increased with silicate application quantity (sodium silicate); slag silicate fertilizer was better than sodium silicate in promoting rice growth. Elevated UV‐B radiation could increase the emission flux and accumulative emission of CH4 in rice soil, but silicate application significantly decreased the emission flux and accumulative emission of CH4 and the methane emission decreased with the increase in silicate application quantity. At one silicate application quantity, slag silicate fertilizer was better than sodium silicate in respect of emission reduction effect. This indicates that application of slag silicate fertilizer in rice production can realize waste reuse and can effectively decrease the CH4 emission in rice field under elevated UV‐B radiation. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd